2017
DOI: 10.1021/acscatal.6b02372
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Ion-Exchanged Cu/Mordenite Catalysts for the Direct Conversion of Methane to Methanol

Abstract: The selective oxidation of methane to methanol is a highly challenging target, which is of considerable interest to gain value-added chemicals directly from fuel gas. Copper-containing zeolites, such as Cu/mordenite, have been currently reported to be the most efficient catalysts for this reaction. In this work, it is shown that solid-state ion-exchanged Cu/mordenites exhibit a significantly higher activity for the partial oxidation of methane to methanol than comparable reference catalysts, i.e., Cu/mordenite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
132
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(148 citation statements)
references
References 67 publications
11
132
0
5
Order By: Relevance
“…It is therefore suggested that the formation of smaller CuO clusters in Cu‐AA/SBA led to the better catalytic performance of Cu‐AA/SBA compared to Cu‐OA/SBA. Calculation of H 2 consumption in the TPR measurements further indicated that, after activation in O 2 , the samples indeed contain Cu II species only as found in Cu/zeolites, which were responsible for activation of methane in earlier studies …”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…It is therefore suggested that the formation of smaller CuO clusters in Cu‐AA/SBA led to the better catalytic performance of Cu‐AA/SBA compared to Cu‐OA/SBA. Calculation of H 2 consumption in the TPR measurements further indicated that, after activation in O 2 , the samples indeed contain Cu II species only as found in Cu/zeolites, which were responsible for activation of methane in earlier studies …”
Section: Resultssupporting
confidence: 87%
“…The last step for extraction of methanol could be performed with liquid water (off‐line extraction) or steam (on‐line extraction). For comparison, Cu/mordenite with a Cu loading of about 2.6 wt %, prepared by a recently reported solid‐state ion‐exchange reaction between NH 4 ‐mordenite and Cu(acac) 2 , was used as a reference zeolite‐based catalyst …”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations